Ethnobotanical Knowledge, Chemistry, and Pharmacology of the Asteraceae Family in Iran: A Review - Nadaf, Mohabat; Halimi Khalil Abad, Majid; Omidipour, Reza; Soorgi, Hamid; Riahi-Madvar, Ali; Saleh Ghamari, Elham (Ethnobotany Research and Applications, 2025)
Background: The Asteraceae family is one of the largest families of flowering plants, known for its diverse chemical compounds with significant biological activities. The majority of Asteraceae family members have therapeutic applications and have a long history in traditional medicine. The purpose of this study is to introduce the key medicinal species of this family and their chemical compounds that are used in traditional Iranian medicine. Methods: Here, we reviewed scientific published studies in major scientific databases on the medicinal and chemical properties of Asteraceae family, emphasizing the ethnobotanical uses in Iran. Results: This review selected 137 key Asteraceae family plants for their medicinal uses and chemical properties. The most frequently used parts were flower (26%) and leaves (21%). The most important preparations were decoction (44%) and infusion (33%). The genus Artemisia participates with the highest number of species (10 species) followed by Centurea (9 species). The most frequently cited medicinal species were used for digestive system treatment (18%) followed by the respiratory system (10%). Among the active substances that determine the biological activity of the plant material phenolic acid derivatives, flavonoids, sesquiterpene lactones and other terpenoids, and polyacetylenes are some of the most commonly reported compounds from Asteraceae family plants. Conclusions: In this research, ethnobotany knowledge about the uses of Asteraceae family plants has been collected so that it will be available to the next generations. Local people are using the plants for various purposes i.e. digestive system treatment, respiratory system, and nervous system. The precious ethnobotanical knowledge about these plants must be transferred to the younger generations. The data may be valuable in the future for pharmacological studies. Keywords: Ethnobotany; Medicinal plants, Asteraceae, Phytochemistry, Plant Ecology.